The Big Move : Life Between the Turning Points - Wyatt-Brown, Anne M., 1939-; Kivnick, Helen Q.; Ray, Ruth E., 1954- (Book collections on Project MUSE., 2016)
When her husband's ill health forces them to move into an assisted living facility, Anne Wyatt-Brown suddenly finds herself surrounded by elderly residents, mostly sick or disabled. In this short but provocative collection, distinguished gerontologists reflect on Anne's moving account of her transition from a vibrant, independent, and scholarly life to one that is quieter, slower, and that takes up considerably less space. By questioning notions of care and community, stigmas of aging, and the psychological factors involved in accepting assistance, this volume provides an instructive framework for thinking about aging, continued care, and our last big move.